Clinical Features and Outcomes of Immunocompromised Children Hospitalized With Laboratory-Confirmed Influenza in the United States, 2011–2015. (25th October 2018) - Collins, Jennifer P; Campbell, Angela P; Openo, Kyle; Farley, Monica M; Cummings, Charisse Nitura; Kirley, Pam Daily; Herlihy, Rachel; Yousey-Hindes, Kimberly; Monroe, Maya L; Ladisky, Macey; Lynfield, Ruth; Baumbach, Joan; et al.
Abstract: Background: Existing data on the clinical features and outcomes of immunocompromised children with influenza are limited. Methods: Data from the 2011–2012 through 2014–2015 influenza seasons were collected as part of the Centers for Disease Control and Prevention (CDC) Influenza Hospitalization Surveillance Network (FluSurv-NET). We compared clinical features and outcomes between immunocompromised and nonimmunocompromised children (<18 years old) hospitalized with laboratory-confirmed community-acquired influenza. Immunocompromised children were defined as those for whom ≥1 of the following applies: human immunodeficiency virus/acquired immunodeficiency syndrome, cancer, stem cell or solid organ transplantation, nonsteroidal immunosuppressive therapy, immunoglobulin deficiency, complement deficiency, asplenia, and/or another rare condition. The primary outcomes were intensive care admission, duration of hospitalization, and in-hospital death. Results: Among 5262 hospitalized children, 242 (4.6%) were immunocompromised; receipt of nonsteroidal immunosuppressive therapy (60%), cancer (39%), and solid organ transplantation (14%) were most common. Immunocompromised children were older than the nonimmunocompromised children (median, 8.8 vs 2.8 years, respectively; P < .001), more likely to have another comorbidity (58% vs 49%, respectively; P = .007), and more likely to have received an influenza vaccination (58% vs 39%, respectively; P < .001) and early antiviral treatment (35% vs 27%, respectively; P = .013). In multivariable analyses, immunocompromised children were less likely to receive intensive care (adjusted odds ratio [95% confidence interval], 0.31 [0.20–0.49]) and had a slightly longer duration of hospitalization (adjusted hazard ratio of hospital discharge [95% confidence interval], 0.89 [0.80–0.99]). Death was uncommon in both groups. Conclusions: Immunocompromised children hospitalized with influenza received intensive care less frequently but had a longer hospitalization duration than nonimmunocompromised children. Vaccination and early antiviral use could be improved substantially. Data are needed to determine whether immunocompromised children are more commonly admitted with milder influenza severity than are nonimmunocompromised children. Abstract : In this cross-sectional study that included 5262 children hospitalized with laboratory-confirmed influenza in the United States over 4 seasons, we found that immunocompromised children were less likely to require intensive care than nonimmunocompromised children, but the other outcomes were similar.